“AMBIENT MISOGYNY”: POCKETS OF GENDERED HATE ACROSS CONTEXTS AND PLATFORMS - Özkula, Suay Melisa; Prieto-Blanco, Patricia; Caldeira, Sofia; Kubrusly, Ana; Ditchfield, Hannah; Vicari, Stefania; Guo, Yumeng (AoIR Selected Papers of Internet Research, 2026)
Recent years have shown renewed scientific interest in online misogyny, albeit predominantly in overt and targeted forms of it. Those include, above all, antifeminist movements and spaces of the manosphere that aim to exploit, suppress, and subjugate women, for example in incel and red pill communities, or masculinity podcasts. This panel applies Siapera’s distinction between ambient and organised digital racism to discuss cases of “ambient misogyny”. Organised hate is typically overt and draws on the networked capabilities of social media platforms to target and harass women or individuals outside of non-heteronormative males. In comparison, ambient misogyny relates to more everyday, banal, and tacit gender talk that may not as easily be identified, considered to be toxic or hateful, or appear in unexpected contexts. Drawing on four case studies in the arenas of health and illness, memetic tropes, feminist content creation, and far right discourses, this panel aims to discuss how ambient misogyny is often overlooked or left unmoderated in light of humour, irony, and sarcasm, women's and non-binary persons' choices for exposure, and normative views on femininity and women's bodies, as well as how the harms resulting from these may be mitigated.